Kajian Yuridis Perlindungan Seimbang Bagi Factor, Client dan Customer Dalam Perjanjian Anjak Piutang (Factoring) - Siti Hamidah (Jurnal Risalah Hukum, 2009)
Factoring stands for one activity of financing agency but unrecognized in the KUHPerdata because it has higher risk susceptibility to the claim failure. Where unperformed client and customer in case of settling the factoring financing debt become evident, the factor company only remains as concurrency creditor. Although the unperformed parties against the content of factoring financing covenant must be customer and client, the factor party should the first priority of protection. Considering the factor as the party who gives financing and binds client through contract-standard covenant, the balancing covenant seems very important because it does not close the possibility of unperformed customer and client due to imbalanced position against factoring covenant. Research analyzes unsuitable clauses or those regarded as not giving balancing protection to factor, client, and customer according to KUHPerdata of factoring covenant and its alternative clauses. In this case, research may suggest that some clauses may stand against KUHPerdata such that it must fail to give balancing protection and position for related parties, in term of interest, fine, and additional collateral. The change over clauses must be important to give balancing protection